Development of Teaching Model for Testing Service Quality and Airport Passenger Satisfaction at Aviation Polytechnic - Nur, Mulyadi; Sabur, Fatmawati; Wahyudi (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: To develop a teaching model that integrates the concepts of service quality testing and airport passenger satisfaction in the educational curriculum at the Aviation Polytechnic. The main focus of the research is to design a competency-based learning approach that covers not only theoretical aspects but also practical applications in the context of the aviation industry. In addition, this research also evaluates the effectiveness of the teaching model in improving students' understanding of airport service quality parameters. Method: used is Research and Development (R&D) with the stages of needs analysis, model design, expert validation, limited trial, and implementation. Data were collected through surveys, interviews with aviation industry stakeholders, as well as pretests and posttests on students to measure the increase in understanding. Data analysis was done quantitatively with descriptive statistics and paired sample t-test, as well as qualitatively through evaluation of learner and expert responses. Results: Showed that the developed teaching model significantly improved students' understanding of airport service quality dimensions such as tangibles, reliability, responsiveness, assurance, and empathy. The effectiveness test of the model shows an increase in understanding scores after implementation. Novelty: Research lies in the integration between the academic curriculum and the real needs of the aviation industry, especially in terms of service quality measurement and passenger satisfaction. The developed model is also equipped with case studies based on actual data from the airport and interactive simulations, thus providing a more contextualised learning experience. This research is expected to be a reference for the development of aviation vocational education curriculum that is more adaptive to industry dynamics.